RNA-Seq combined with population-level analysis reveals important candidate genes related to seed size in flax (Linum usitatissimum L.) - Jiang, Haixia; Guo, Dongliang; Liu, Yuanyuan; Zhu, Leilei; Xie, Fang; Xie, Liqiong (Frontiers in Plant Science, 2022)
Seed size is a key determinant of crop yields. Understanding the regulatory mechanisms of seed size is beneficial for improving flax seed yield. In this study, the development of large flax seeds lagged behind that of small seeds, and 1751 protein-coding genes were differentially expressed in early seeds, torpedo-stage embryos and endosperms of CIli2719 and Z11637 using RNA sequencing. Homologous alignment revealed that 129 differentially expressed genes (DEGs) in flax were homologous with 71 known seed size-related genes in Arabidopsis thaliana and rice (Oryza sativa L.). These DEGs controlled seed size through multiple processes and factors, among which phytohormone pathways and transcription factors were the most important. Moreover, 54 DEGs were found to be associated with seed size and weight in a DEG-based association study. Nucleotide diversity (π) analysis of seed size-related candidate DEGs by homologous alignment and association analysis showed that the π values decreased significantly during flax acclimation from oil to fiber flax, suggesting that some seed size-related candidate genes were selected in this acclimation process. These results provide important resources and genetic foundation for further research on seed size regulation and seed improvement in flax.